Islamic Education in the Face of Globalization and Modernization Challenges - Sitti, Metin; Rosyalita, Dita (Jurnal Ar Ro'is Mandalika (Armada), 2025)
This literature review examines the challenges and opportunities faced by Islamic education in the context of globalization and modernization. The integration of Islamic values with modern educational systems is a pressing concern, as globalization and modernization pose significant challenges to traditional Islamic educational frameworks. The review synthesizes existing research on how Islamic education can adapt to these changes while maintaining its core principles. It explores the tensions between preserving cultural and religious identity and embracing modern pedagogies and technologies. The study also discusses potential strategies for enhancing Islamic education's relevance and effectiveness in a rapidly changing world. By analyzing the current state of research, this review aims to inform educators, policymakers, and scholars about best practices for navigating the complexities of globalization and modernization in Islamic education.